Preparation and application of a thidiazuron·diuron ultra-low-volume spray suitable for plant protection unmanned aerial vehicles - Qin Liu (Nature Portfolio, 2021)
Abstract Spraying of defoliant can promote centralized defoliation of cotton and advance maturity to facilitate harvesting. Modern pesticide application equipment includes plant protection unmanned aerial vehicles (UAVs), which are used widely for spraying defoliants. However, commonly used defoliant formulations are mainly suspension concentrates and water-dispersible granules, which need to be diluted with water when used. These are not suitable for plant protection UAVs with limited load capacity, especially in arid areas such as Xinjiang, China. Therefore, we prepared a thidiazuron·diuron ultra-low-volume (ULV) spray, which can be used directly without dilution in water. We found that ULV sprays had better wettability than the commercially available suspension concentrate, could quickly wet cotton leaves and spread fully. The volatilization rate was lower. ULV sprays also showed better atomization performance and more uniform droplet distribution than the commercially available suspension concentrate. At a dosage of 4.50–9.00 L/ha, the coverage rate on cotton leaves was 0.85–4.15% and droplet deposition densities were 15.63–42.57 pcs/cm2; defoliation rate and spitting rate were also greater than those of the reference product. This study could be contributed to the development of special pesticide formulations suitable for UAVs.